An assessment of CFD applied to steady flow in a planar diffuser upstream of an automotive catalyst monolith - Porter, Sophie; Mat Yamin, Ahmad Kamal; Aleksandrova, Svetlana; Benjamin, Stephen; Roberts, Carol A.; Saul, Jonathan (SAE International, 2014)
Flow maldistribution across automotive exhaust catalysts significantly affects their conversion efficiency. Flow behaviour can be predicted using computational fluid dynamics (CFD). This study investigates the application of CFD to modelling flow in a 2D system consisting of a catalyst monolith downstream of a wide-angled planar diffuser presented with steady flow. Two distinct approaches, porous medium and individual channels, are used to model monoliths of length 27 mm and 100 mm. Flow predictions are compared to particle image velocimetry (PIV) measurements made in the diffuser and hot wire anemometry (HWA) data taken downstream of the monolith. Both simulations compare favourably with PIV measurements, although the models underestimate the degree of mixing in the shear layer at the periphery of the emerging jet. Tangential velocities are predicted well in the central jet region but are overestimated elsewhere, especially at the closest measured distance, 2.5 mm from the monolith. The individual channels model is found to provide a more consistently accurate velocity profile downstream of the monolith. Maximum velocities, on the centre line and at the secondary peak near to the wall, are reasonably well matched for the cases where the flow is more maldistributed. Under these conditions, a porous medium model remains attractive because of low computational demand.